KUALITAS PELAYANAN PEMBUATAN AKTA KEMATIAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PALU - Rizaldy, Fuad; Sastrio, Sastrio; Patunrangi, Hajar Anna (Katalogis, 2020)
The purpose of this study was to determine the Quality of Service for Making Deed of Death at the Population and Civil Registration Office of the City of Palu. The theoretical foundation used is Parasuraman and Berry (1990) to see the quality of service using indicators of tangibles, reliability, assurance, and empathy. This type of research is Qualitative Descriptive which seeks to describe and pour data that is pleasing to the facts, using purposive methods, data cursing and discussion with the type of qualitative research. Meanwhile, discussing data and materials through observation and interviews with 6 (six) informants.Based on the results of research that shows the Quality of Service for Making Deed of Death in the Population and Civil Registration Office of the City of Palu has not run optimally. This is due to the five indicators, namely Reliability, Responsiveness, and Guarantees have been running optimally. However, two indicators namely Tangibles and Empathy have not run optimally because the level of service satisfaction is very unsatisfactory or inappropriate for the community, as well as Physical Appearance for facilities and infrastructure provided by the Palu City Population and Civil Registration Service in Central Sulawesi. and does not meet service standards in terms of providing special and special rooms in the process of providing services, as well as the dimensions of Empathy that are in the process of providing services